PENINGKATAN KINERJA GURU TIDAK TETAP (GTT) DI SMP NEGERI LAMBANDIA SULAWESI TENGGARA MEALUI MASA KERJA, KOMPENSASI, KOMPETENSI DAN KEPUASAN KERJA - Hendra Haris (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2014)
This study was conducted to test the hypothesis, with the intention of confirming or strengthening the hypothesis that in turn can reinforce theories that became the foundation. In this regard, researchers tried to examine the effect of tenure, compensation and competencies to job satisfaction and the unconstant teachers performance in Junior High Schools Lambandia. Population and sample in this study is the overall unconstant teachers in Junior High Schools Lambandia totaling 75 people. The study was conducted by survey method by distributing koesioner to the respondents. Statistical tool used is multiple regression, the data were analyzed further using smartPLS application. Analysis of the results showed that: (1) Tenurehas a negative and no significant effect on job satisfaction, (2) Compensation has a positive and significant effect on job satisfaction, (3) Competence has a positive and significant effect on job satisfaction, (4) affect job satisfaction positive and significant impact on performance (5) Tenure has a positive and no significant effect on performance, (6) Compensation has a negative and no significant effect on performance, (7) Competence has a positive and significant effect on performance.Keywords : Tenure, Compensation, Competence, Job Satisfaction and Unconstant Teacher Performance